2002
DOI: 10.1128/cmr.15.3.465-484.2002
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Nonculture Methods for Diagnosis of Invasive Fungal Infections

Abstract: The incidence of invasive fungal infections has increased dramatically in recent decades, especially among immunocompromised patients. However, the diagnosis of these infections in a timely fashion is often very difficult. Conventional microbiologic and histopathologic approaches generally are neither sensitive nor specific, and they often do not detect invasive fungal infection until late in the course of disease. Since early diagnosis may guide appropriate treatment and prevent mortality, there has been cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
176
1
20

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(202 citation statements)
references
References 243 publications
1
176
1
20
Order By: Relevance
“…While these antibody-based assays have a number of applications they can yield false positives and may also fail to detect infection where shedding of cell wall material has not occurred (Yeo and Wong, 2002). A number of protein or non-proteinaceous toxins produced by A. fumigatus play a crucial role in assisting the fungus to colonise and penetrate pulmonary tissue and may be detected in blood, urine or sputum specimens (Amitani et al, 1995a;Daly and Kavanagh, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these antibody-based assays have a number of applications they can yield false positives and may also fail to detect infection where shedding of cell wall material has not occurred (Yeo and Wong, 2002). A number of protein or non-proteinaceous toxins produced by A. fumigatus play a crucial role in assisting the fungus to colonise and penetrate pulmonary tissue and may be detected in blood, urine or sputum specimens (Amitani et al, 1995a;Daly and Kavanagh, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Woo et al (2002) have developed ELISA systems which detect A. fumigatus galactomannan (Afmp1p) and anti-Afmp1p antibody in invasive aspergillosis patients resulting in a combined sensitivity of 86.7%. Although the application of Aspergillus DNA detection systems has proven useful in terms of correlation in fungal DNA reduction with disease resolution and treatment efficacy, the inability of nucleic acid-based systems to differentiate between (i) fungal strains and (ii) colonisation and infection remains problematical (Yeo and Wong, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,10,20 Fortunately, in the current study, the fungemia-associated attributable mortality (15%) was found to be low among neutropenic allogeneic stem cell transplantation recipients who did not receive antifungal therapy and suggests that most fungal blood isolates (85%), even in a highly susceptible group, were "clinically nonsignificant" and most likely represented environmental contamination (Table 2). [2][3][4] Diagnostic parameters for "probable" fungemia are arbitrary; therefore, surrogate diagnostic markers 21 are needed critically to reduce the variability in interpretations of clinical data and the inconsistencies in decisions to either withhold or institute effective therapy. The current criteria, which are far from satisfactory, suggest probable systemic mycoses; they include 1) an immunologically susceptible host (severe granulocytopenia, cellular immune dysfunction, or both), 2) breakthrough fungal infections in patients receiving subtherapeutic antifungals as prophylaxis, and 3) radiographic and clinical features consistent with fungal tissue invasion and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 50 years, different strategies have been devel-oped including detection of antibodies, antigens, and nonantigenic fungal components such as DNA, D-arabinitol, and b-1,3-D glucan [50][51][52]. Once the genome of C. albicans was sequenced and microarrays had been developed, the technology was used to study different aspects of its biology.…”
Section: Candida Albicansmentioning
confidence: 99%